2019
DOI: 10.3390/ijerph16081351
|View full text |Cite
|
Sign up to set email alerts
|

Amputation Risk Factors in Severely Frostbitten Patients

Abstract: In recent years, the incidence of frostbite has increased among healthy young adults who practice winter sports (skiing, mountaineering, ice climbing and technical climbing/alpinism) at both the professional and amateur levels. Moreover, given that the population most frequently affected is healthy and active, frostbite supposes a substantial interruption of their normal activity and in most cases is associated with long-term sequelae. It particularly has a higher impact when the affected person’s daily activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Injured tissue could, to some extent, be saved with advanced hospital care, although the level and duration of the in-freeze situation, among other factors is decisive [ 38 , 39 , 43 ]. Surgical amputation decisions are determined in part by altitude as the most relevant amputation risk factor derived from a stepwise regression model [ 44 ]. The Yukon Frostbite Protocol relies on the Cauchy system of frostbite grading to determine treatment [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Injured tissue could, to some extent, be saved with advanced hospital care, although the level and duration of the in-freeze situation, among other factors is decisive [ 38 , 39 , 43 ]. Surgical amputation decisions are determined in part by altitude as the most relevant amputation risk factor derived from a stepwise regression model [ 44 ]. The Yukon Frostbite Protocol relies on the Cauchy system of frostbite grading to determine treatment [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The waiting period (weeks or months), necessary to determine the amputation level, is likely to cause mental anguish for the patient. FCI symptoms such as numbness and coldness of the injured part have been regarded as secondary clinical signs and symptoms, after vasoconstriction and ischaemia, because they are usually of little help for predicting prognosis before rewarming [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hostile environmental conditions at high altitude or when performing mountain sports in the winter are associated with the risk to suffer from frostbite and/or hypothermia, frequently resulting in adverse long-term consequences or even death. Carceller and colleagues evaluated factors related to the risk of amputation in patients who suffered from severe frostbite [ 5 ]. Regression analysis revealed the mountain range, years of expertise in winter mountaineering, time elapsed before rewarming, and especially altitude as the most important factors for a poor prognosis.…”
Section: Frostbites Skeletal Muscle and Kidney Injuriesmentioning
confidence: 99%
“…Frostbite injury, once considered a military phenomenon, has become more common in the civilian population, with increased incidence among homeless individuals, industrial workers, and people engaging in cold weather recreational activities. [1][2][3][4] Although data on the overall incidence of frostbite are limited, a retrospective study of 241 patients reported a 3% mortality rate. In the same study, however, surgical intervention with debridement and/or amputation was required in 20% of patients.…”
Section: Introductionmentioning
confidence: 99%